Resilient patriarchy: public authority and women's (in)security in Karamoja, Uganda. (27th December 2017) - Hopwood, Julian; Porter, Holly; Saum, Nangiro
Abstract : This paper draws on fieldwork conducted in 2011 and 2016 to explore the differing experiences of Karamojong women following the Government of Uganda's most recent disarmament programme. Besides being deprived of their guns, Karamojong communities have lost most of the cattle on which their livelihoods and way of life were centred. The study assesses whether or not women's experience of patriarchy has changed in these new circumstances, and, if so, how this impacts on their security and control of resources, or the absence of them. It maps, using information primarily supplied by women, public authorities from below, and evaluates if and how they respond to women's protection and survival needs, as well as if current development/humanitarian interventions are of sustainable benefit to Karamojong women. The paper concludes that apparent shifts in gender relations are probably superficial, contingent on continuing food aid, and that economic development and positive social change for women remain elusive.